Intracellular growth factors in polycythemia vera and other myeloproliferative disorders. - Eid, J (1987)
In polycythemia vera, idiopathic myelofibrosis, and essential thrombocytosis, hematopoietic cell proliferation is increased in the absence of a recognizable stimulus, suggesting the autonomous production of growth factors in these disorders. Sonicates of peripheral blood mononuclear cells (PBMNC) from patients with polycythemia vera, idiopathic myelofibrosis, and essential thrombocytosis contained soluble factors that stimulated the proliferation of quiescent-confluent 3T3 cells. PBMNC sonicates from normal individuals; from patients with secondary erythrocytosis, chronic myelogenous leukemia, B-cell chronic lymphocytic leukemia, and acute myelogenous leukemia; and from K-562 and HL-60 cells did not stimulate proliferation. Polycythemia vera PBMNC sonicates also induced anchorage-independent colony formation in soft agar by normal rat kidney fibroblasts. Both the mitogenic and transforming activities of the polycythemia vera PBMNC sonicates resided in the T-lymphocyte-depleted mononuclear fraction of the PBMNC and were not secreted. By gel filtration, reversed-phase HPLC and NaDodSO4/PAGE, the mitogenic and transforming activities in the polycythemia vera PBMNC were localized to three proteins with molecular masses of 13-, 17-, and 65-kDa. The 13-kDa protein was only mitogenic, and the 17-kDa protein was only transforming, whereas the 65-kDa protein had both mitogenic and transforming activity. These proteins may be involved in the autonomous hematopoiesis that characterizes polycythemia vera, idiopathic myelofibrosis, and essential thrombocytosis.